IMPLEMENTATION OF INDEPENDENT LEARNING CURRICULUM IN THE PERSPECTIVE OF PROGRESSIVISM PHILOSOPHY - Cahayani, Ni Luh Putu; Suastra, I Wayan (Indonesian Journal of Educational Development (IJED), 2024)
The aim of this research is to determine the implementation of independent learning curriculum from the perspective of John Dewey's progressivism philosophy. This research was carried out using a library research approach to explain relevant concepts. The research approach uses a descriptive qualitative approach. The research results that the independent learning curriculum initiated by the Minister of Education, Culture, Research and Technology is in line with the flow of progressivism. The independent curriculum provides freedom for students and teachers in expressing ideas and expressions. The characteristics of an independent curriculum include project learning, essential material, and flexibility.